Scattering Cancellation Coating Composed of Periodical Subwavelength Structures - Kan, Weiwei; Tian, Cong; Chen, Yikai (Frontiers in Physics, 2022)
We propose to cancel the scattered wave using two layers of periodical subwavelength structures by coating the scattering object with the designed composite material. As a demonstration, it is possible to obtain such scattering cancellation effect for a fiber optical nanoprobe, and fabricate the coating layers by simply etching cylinders or doping elements in silicon/SOI wafer. The required quasistatic parameters of the coating material are homogeneous and isotropic. The simulation results show that the 632.8 nm TE polarized light travels through the coated fiber optical nanoprobe with the wavefront undisturbed, and serve as evidence of the effectiveness of the designed invisibility coating. The proposed scattering cancellation scheme could be useful in non-invasive probing applications at visible and near-infrared wavelengths.